Dermatoglyphics patterns in patients suffering from primary amenorrhea and control population - Sushil Jiwane; Vivekanand Gajbhiye; Rekha Jiwane (International Journal of Medical Research and Review, 2017)
Background: Dermatoglyphics is branch of medical science, which deals with the study of epidermal ridges and their configuration on the palmer region of hand and finger and planter region of foot and toes. Inspection of skin ridges provide a simple, inexpensive means of information to determine whether a given patient could have a particular chromosomal defect. Amenorrhea is defined primary when menarche does not occur by the age of 16 years in a girl with complete secondary sexual development. In the present study an attempt has been made to correlate primary amenorrhea and dermatoglyphics.Method: 40 normal females with primary amenorrhea were taken as case and 40 normal females with normal menstrual cycle were taken for study. Dermatoglyphic prints were obtained using ink method.Result: The mean value of atd angle shows statistically significant increase in patients than that of controls. Frequency of thenar/ ID1 pattern, ID2area, ID3area, IDarea in a both right and left hands of primary amenorrhea patients and in control is insignificant. Similarly, there is increased frequency of hypothenar area pattern in patients as compared to controls in left hand, which is found to be statistically significant.Conclusion: Primary amenorrhoea and Dermatoglyphics, both have the suspected multifactorial (genetic and environmental) aetiologies. Dermatoglyphics, due to their suspected genetic aetiology. use for prognosis of disease and also the identification of people with the genetic predisposition to develop certain disease or early onset of symptoms.